Synthesis and characterization of MgO nanopowders by sol-gel method incorporated reflux approach / Noraziahwati Ibrahim - Ibrahim, Noraziahwati (2010)
Magnesium oxide powders have been prepared by sol-gel method in reflux condition. The powders are synthesized using magnesium acetate tetrahydrate and oxalic acid as precursors with ethanol as a solvent. The concentration of the oxalic acid have been varied which are 0.5 M and 1.0 M. All the sol-gel products were annealed at 600 ºC, 700 ºC and 800 ºC for 6 hours. The annealed products were systematically investigated by Thermogravimetric Analyzer (TGA), X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). The effects of annealing temperature and the concentration of oxalic acid onto phases and morphologies of MgO were investigated throughout this study. Thermogravimetric analysis provided insight into the decomposition process of the magnesium acetate tetrahydrate. The XRD analysis indicates that all the products were of cubic lattice with increasing degree of crystallinity when increased the annealing temperatures. Besides that, the crystallite sizes of MgO were increased due to increasing of annealing temperatures and the concentration of oxalic acid. In this study, the crystallite size of the MgO products was in a range from 13.5 nm to 22.7 nm. The morphology of MgO was nanospheres